2018
DOI: 10.1371/journal.pone.0193594
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of human bocavirus in Saudi healthy blood donors

Abstract: Human bocavirus is associated with respiratory disease worldwide, mainly in children. There are conflicting results, however, regarding the existence of the HBoV in blood donors. Three hundred whole blood samples from non-immunodeficient healthy blood donors were screened for the presence of HBoV by polymerase chain reaction. The HBoV genotype of positive samples was determined using direct gene sequencing. Twenty-one out of the three hundred blood samples were found to be positive for HBoV. Sequence analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
(32 reference statements)
0
6
2
Order By: Relevance
“…In this study, the mixed infection rate of HBoV with other viruses was 25%, which is much lower than the mixed viral infection rate of HBoV in most studies of nasopharyngeal swab samples at this stage, including Moreno et al ( 2016 ) (54.5%) in Panama, Lekana-Douki et al ( 2018 ) (84.4%) in Gabon, and Calvo et al ( 2016 ) (75%) in Spain. Notably, the single viral infection rate in this study is much higher than that in similar studies (Abdel-Moneim et al, 2018 ; Abozahra et al, 2020 ; Madi and Al-Adwani, 2020 ; Ji et al, 2021 ). In the absence of serological confirmation and lack of evidence of viremia or HBoV mRNA in peripheral blood cells, we still cannot rule out the possibility that the high detection rate of HBoV monoinfection was caused by a recent HBoV infection or persistent HBoV1 viral shedding in the upper respiratory tract of the Qingdao hospitalized children enrolled in this study.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…In this study, the mixed infection rate of HBoV with other viruses was 25%, which is much lower than the mixed viral infection rate of HBoV in most studies of nasopharyngeal swab samples at this stage, including Moreno et al ( 2016 ) (54.5%) in Panama, Lekana-Douki et al ( 2018 ) (84.4%) in Gabon, and Calvo et al ( 2016 ) (75%) in Spain. Notably, the single viral infection rate in this study is much higher than that in similar studies (Abdel-Moneim et al, 2018 ; Abozahra et al, 2020 ; Madi and Al-Adwani, 2020 ; Ji et al, 2021 ). In the absence of serological confirmation and lack of evidence of viremia or HBoV mRNA in peripheral blood cells, we still cannot rule out the possibility that the high detection rate of HBoV monoinfection was caused by a recent HBoV infection or persistent HBoV1 viral shedding in the upper respiratory tract of the Qingdao hospitalized children enrolled in this study.…”
Section: Discussioncontrasting
confidence: 70%
“…The overall detection rate of HBoV was 28.1%, which was significantly higher than that reported by Ji et al (2021) (10.0%) who tested lower respiratory tract samples of 878 children in Ningxia and also significantly higher than that of Saudi Arabia (7%) (Abdel-Moneim et al, 2018), Kuwait (1.9%) (Madi and Al-Adwani, 2020), and the United Kingdom (8.66%) (Bagasi et al, 2020). This is slightly lower than the detection rate of HBoV (51.7%) reported by Petrarca et al (2020) who tested samples of 60 children with ARI in the Rome area.…”
Section: Discussioncontrasting
confidence: 62%
“…Alternatively, our data could point to a stage of viraemia that occurs after HBoV1 locates in the target organ (the respiratory tract), sometimes spanning the clinical manifestations but preferentially beyond. In this scenario, detection of the HBoV1 genome in serum of asymptomatic individuals, even adults, or in individuals with other pathologies [43–46]⁠ should be considered. Analysis of cases of acute gatroenteritis and HBoV1+ detection in serum and stool might be of particular interest in this regard [47, 48]⁠.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the research carried out in China, 9.06% of healthy plasma donors were HBoV DNA positive. In the study carried out by an Italian research group, HBoV DNA was found in 5.51% of serum samples of apparently healthy blood donors, but in the study done in Saudi Arabia, 7.0% of blood donors showed HBoV viremia [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%